The language of feelings: A reading and storytelling group in an adolescent unit. (October 2015) - Killick, Steve; Bowkett, Steve
This article describes a "Reading and Storytelling Group" that ran at an adolescent inpatient unit and outlines how fictional stories, both read and told, can develop psychological insights such as mentalization and emotional literacy. The structure of the group is described, and some of the activities and responses of the young people are illustrated. How activities such as this can have therapeutic benefits without being ostensibly "therapy" are discussed.